FACTORS INFLUENCING THE ADOPTION OF E-TILANG; EMPIRICAL EVIDENCE FROM THE UTAUT MODEL - Eva, Yumami; Setyohadi, Djoko Budiyanto; Suyoto, Suyoto (Journal of process management and new technologies, 2018)
Mid-Year 2017 The National Police of the Republic of Indonesia publishes E-tilang technology innovation. E-tilang is a mobile app that is used online by traffic police to take action against traffic violators on the highway. E-tilang aims to improve service to the public and reduce the misuse fines of traffic violations. This research factor influences acceptance and use of e-ticket by using UTAUT model. This research was conducted in Bengkulu area with 152 traffic policemen. The findings of this study indicate that performance expectancy, effort expectancy, and social influences positively affect the use of E-tilang. Facilitating conditions has no significant effect on the intention of using E-tilang. The results of this study are important steps to improve E-tilang services.